2014
DOI: 10.1016/j.neuropsychologia.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

ERP abnormalities elicited by word repetition in fragile X-associated tremor/ataxia syndrome (FXTAS) and amnestic MCI

Abstract: Background: Fragile X-associated tremor/ataxia syndrome (FXTAS), a neurodegenerative disorder caused by FMR1 gene premutations, typically associated with frontal-subcortical type cognitive impairments. High prevalence (~50%) of superimposed Alzheimer’s pathology has been reported in FMR1 premutation carriers, and standardized neuropsychological tests have not yielded any robust discriminators between FXTAS and Alzheimer’s disease (AD) dementia. The similarities/differences in memory processes between FXTAS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Only one previous controlled trial has been performed in individuals with FXTAS, a memantine trial lasting 1 year, but this treatment did not improve tremor, ataxia, or executive function [22]. However, we found that the N400 repetition effect amplitude, thought to index semantic processing and verbal learning/memory, displayed improvements after the memantine treatment compared with placebo, and predicted verbal learning and memory performance in the FXTAS group (but not in a group with prodromal/early Alzheimer disease) [60,61]. The results suggest that the N400 repetition effect, primarily originating from the temporal neocortex [62,63], is sensitive to memory changes in FXTAS.…”
Section: Discussionmentioning
confidence: 59%
“…Only one previous controlled trial has been performed in individuals with FXTAS, a memantine trial lasting 1 year, but this treatment did not improve tremor, ataxia, or executive function [22]. However, we found that the N400 repetition effect amplitude, thought to index semantic processing and verbal learning/memory, displayed improvements after the memantine treatment compared with placebo, and predicted verbal learning and memory performance in the FXTAS group (but not in a group with prodromal/early Alzheimer disease) [60,61]. The results suggest that the N400 repetition effect, primarily originating from the temporal neocortex [62,63], is sensitive to memory changes in FXTAS.…”
Section: Discussionmentioning
confidence: 59%
“…For the final words of the sentences, the FN400 and LPC were analyzed. The components' mean amplitudes for the final words followed by the response time window was qualified based on the findings of the previous literature (e.g., Danko et al, 2014;Molinaro et al, 2016;Yang et al, 2014;Volz et al, 2019) as the mean voltage between 300 to 550 ms…”
Section: The Eeg Recordingmentioning
confidence: 99%
“…The N400 effect is a well-established electrophysiological index of semantic priming and semantic processing load. Yang et al (2014a) have found that the N400 repetition effect amplitude is the strongest predictor of the CVLT short delay cued recall score in patients with FXTAS and was correlated significantly with all 6 CVLT measures of verbal learning and memory in the FXTAS group, but not in a group with prodromal/early AD. These authors suggested that the N400 repetition effect, shown to primarily originate from temporal neocortex ( Nobre et al, 1994 ; Halgren et al, 2002 ), has substantial association with learning/acquisition and short delayed recall, and is sensitive to memory dysfunction in FXTAS.…”
Section: Discussionmentioning
confidence: 93%